Aurantio-obtusin modulates Wilms Tumour 1 within the breast tumour microenvironment reducing immunosuppression and tumour growth - Rui Li; Dómhnall J O’Connor; Barry Digby; Pilib Ó. Broin; Xiao Hu; Ning Ge; Paul G. Loftus; Vatsal Kumar; Eoin McEvoy; Stephen J. Elliman; Michael J. Kerin; Laura R. Barkley (Cell Communication and Signaling)
Abstract Introduction Cancer associated fibroblasts (CAFs) contribute to tumourigenesis and immune tolerance within the tumour microenvironment (TME). Therefore, inhibiting the pro-tumourigenic function of CAFs can be a viable therapeutic approach. However, targeting CAFs is challenging due to the lack of specific markers. The objective of this study is to identify CAF specific therapeutic targets that have the potential to enhance tumour immunity and reduce tumour growth. Methods RNA sequencing was performed on CAFs and normal fibroblasts (NFs) from the same breast cancer patient. Wilms tumour-1 (WT1) was identified as a gene upregulated in CAFs. WT1 levels in CAFs were manipulated using plasmid overexpression of—or siRNA downregulation of WT1. Co-culture assays were performed to evaluate the role of CAF-derived WT1 in T cell proliferation and differentiation using flow cytometry. Western blot and ELISA were performed to interrogate the mechanism of action of WT1 within CAFs. Three-dimensional patient-derived organoids (PDOs) that encompassed the tumour immune-microenvironment were established to determine the therapeutic potential of targeting CAF-derived WT1. Results WT1, a transcription factor, regulates signal transducer and activator of transcription (STAT) 1/3 levels, promotes programmed death ligand 1 (PD-L1) expression and indoleamine 2,3-dioxygenase (IDO) expression in CAFs. CAF-derived WT1 reduces the proliferation of CD4+ and CD8+ T cells and enhances the differentiation of naïve T cells into regulatory T cells (Tregs), thus producing an immunosuppressive TME. Reducing CAF WT1 levels results in less immunosuppressive CAFs, smaller PDOs and increased levels of cytotoxic granzyme B+ (GZMB+) T cells within the TME. Standard chemotherapeutic agents, paclitaxel (PTX) and doxorubicin (DOX), increase WT1 levels in CAFs enhancing their ability to suppress T cell proliferation. However, Aurantio-obtusin (AO, a DOX analogue) decreases WT1 expression in CAFs reducing their ability to suppress T cell proliferation. AO causes decreased PDO size which correlates with increased levels of T cells within the TME. Conclusions Therapeutic targeting of the WT1/STAT1/3/PD-L1/IDO axis in CAFs with AO has the potential to enhance T cell activity and reduce Treg percentage within the TME, thereby enhancing tumour immunity and reducing tumourigenesis.